Implementation of Enterprise Risk Management as a Strategy for Increasing Competitive Advantage: Study at Companies in Central Kalimantan - Yuwono, Matias Andika; Ellitan, Lena (UUM Press, 2025)
This research investigated the impact of Enterprise Risk Management (ERM) and organizational culture on competitive advantage (CA) in cigarette companies in Kalimantan. Through in-depth interviews with three key informants (a branch manager, a sales supervisor, and a finance account manager), the study revealed that effective ERM, particularly in managing external risks like regulatory changes and market fluctuations and internal risks such as operational challenges and HR issues, is crucial for achieving CA. Additionally, an organizational culture that fosters innovation, risk-based performance assessment, and effective HR management significantly contributes to the success of ERM and strengthens CA. Companies can better manage risks and enhance their competitive position by adapting to market changes and embracing innovation. While this research offers valuable insights, its generalizability may be limited due to its focus on cigarette companies in Central Kalimantan and its relatively small sample size. Future research could broaden the scope to include a broader range of companies and regions to gain a more comprehensive understanding. This study's original contribution lies in exploring the interplay between ERM and organizational culture in the context of CA in the cigarette industry. The findings emphasize the importance of integrating risk management and organizational culture as a strategic approach to maintain and strengthen competitive advantage, providing valuable implications for research and practice in this field